A Glutamine Insertion at Codon 432 of RpoB Confers Rifampicin Resistance in Mycobacterium tuberculosis - Lai, Li-Yin; Hsu, Li-Yu; Weng, Shang-Hui; Chung, Shuo-En; Ke, Hui-En; Lin, Tzu-Lung; Hsieh, Pei-Fang; Lee, Wei-Ting; Tsai, Hsing-Yuan; Lin, Wan-Hsuan; Jou, Ruwen; Wang, Jin-Town (Frontiers in Microbiology, 2020)
Tuberculosis (TB) is an infectious respiratory disease caused by Mycobacterium tuberculosis and one of the top 10 causes of death worldwide. Treating TB is challenging; successful treatment requires a long course of multiple antibiotics. Rifampicin (RIF) is a first-line drug for treating TB, and the development of RIF-resistant M. tuberculosis makes treatment even more difficult. To determine the mechanism of RIF resistance in these strains, we searched for novel mutations by sequencing. Four isolates, CDC-1, CDC-2, CDC-3, and CDC-4, had high-level RIF resistance and unique mutations encoding RpoB G158R, RpoB V168A, RpoB S188P, and RpoB Q432insQ, respectively. To evaluate their correlation with RIF resistance, plasmids carrying rpoB genes encoding these mutant proteins were transfected into the H37Rv reference strain. The plasmid complementation of RpoB indicated that G158R, V168A, and S188P did not affect the MIC of RIF. However, the MIC of RIF was increased in H37Rv carrying RpoB Q432insQ. To confirm the correlation between RIF resistance and Q432insQ, we cloned an rpoB fragment carrying the insertion (encoding RpoB Q432insQ) into H37Rv by homologous recombination using a suicide vector. All replacement mutants expressing RpoB Q432insQ were resistant to RIF (MIC > 1 mg/L). These results indicate that RpoB Q432insQ causes RIF resistance in M. tuberculosis.